Representação feminina nas HQSs e a construção de identidade : a personagem Wonder Woman como símbolo de empoderamento feminino - Santos, Waleska da Graça (2018)
In the process of identity construction, the media and entertainment industry act as tools that contribute to the formation of the individual. These media are responsible for reflecting stereotypes that make up society and often the subjective way exposed by these channels of communication reproduce a unilateral view of society, which on many occasions have privileged the eyes of those who hold the domain of the word. Among the many categories objectified and/or erased by these means are the women. Female stereotypes, though many are not diversified, women are always represented as: the mother, the wife, the damsel in distress, the mistress among others, all those created to establish the place of women in society. The struggle for female visibility is not recent and one of the reasons for this struggle is the way women are represented in the media. The present work aims to analyze and discuss how women are represented in the genre Comics, so we will analyze the character Wonder Woman, who despite being seen as a symbol of female empowerment, carries several marks of the male view upon the woman. The methodology adopted to conduct this work will be through qualitative bibliographical research. The development of the analyzes proposed by this work will follow some theoretical perceptions among which are the Multimodal Theory of Speech by Kress and Van Leewen (2001) and Van Leewen (2005), The performative Theory by Butler (1990) and the Identity Studies by Hall (2000). The reading of the images that compose the genre analyzed will also use the contribution of the Critical Literacy and the Cultural Studies. The need to redefine the female image in the universe of comics is the central aim of this work.